2005
DOI: 10.1002/jmri.20247
|View full text |Cite
|
Sign up to set email alerts
|

3.0‐Tesla MR angiography of intracranial aneurysms: Comparison of time‐of‐flight and contrast‐enhanced techniques

Abstract: Purpose: To determine whether 3.0-T elliptical-centric contrast-enhanced (CE) magnetic resonance (MR) angiography is superior to 3.0-T elliptical-centric time-of-flight (TOF) MR angiography in the detection and characterization of intracranial aneurysms, and to determine whether increasing the acquisition matrix size in 3.0-T CE MR angiography improves image quality. Materials and Methods:A total of 50 consecutive patients referred for MR angiographic evaluation of a known or suspected intracranial aneurysm un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 9 publications
(13 reference statements)
0
33
0
Order By: Relevance
“…In another familial IA screening study, 13 of the 43 DS angiograms performed to confirm the MR angiography findings, 7 (16%) of 43 were negative, with the suspected IA later found to be a vessel loop. It is noteworthy that the prior study was performed > 10 years ago and that current MR angiography screening probably has a higher specificity and sensitivity, 5,6 even for very small aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another familial IA screening study, 13 of the 43 DS angiograms performed to confirm the MR angiography findings, 7 (16%) of 43 were negative, with the suspected IA later found to be a vessel loop. It is noteworthy that the prior study was performed > 10 years ago and that current MR angiography screening probably has a higher specificity and sensitivity, 5,6 even for very small aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The inter-observer agreement in defining IA in asymptomatic patients is excellent, and more recent advances in MR angiography have further improved this interobserver agreement, even among small aneurysms. 5,6 Intraarterial cerebral arteriography remains the gold standard for aneurysm detection, but does entail a low risk of stroke and other complications. Arteriographic confirmation of the aneurysm's presence was not required for the current study.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…It has been shown that TOF-MRA is a sensitive and safe technique regarding coiled aneurysms; some authors have concluded that it may be even more sensitive than DSA [5,9,[17][18][19][20][21]. Others recommend CE-MRA or contrastenhanced TOF-MRA to raise sensitivity regarding residual filling and to minimize stent-related artifacts [6,7,9,22,23]. In our relatively small collective, more neck remnants were detected in TOF-MRA than in DSA.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a good correlation with a magnetic resonance angiography (MRA) obtained on the same occasion, follow-up is continued by MRA at regular intervals. With regard to current publications, it is discussed controversially whether TOF-MRA or contrast-enhanced MRA (CE-MRA) is the superior technique for aneurysm follow-up [6,7]. Other authors recommend contrastenhanced TOF-MRA to enhance the sensitivity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The SNR can be expected to be twice as high at 3.0 T as at 1.5 T. This higher SNR could be theoretically used to obtain higher temporal or spatial resolution imaging or a reduction in scan time. For this reason, 3.0 T imaging has established applications in the neuroradiologic field (25,26). However, there are many problems associated with 3.0 T imaging particularly for the abdomen and pelvis (13,27,28).…”
Section: T Mri Of the Abdomen And Pelvis In Clinical Settingsmentioning
confidence: 99%